2017
DOI: 10.1007/s10620-017-4564-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial: Esomeprazole, Bismuth, Levofloxacin, and Amoxicillin or Cefuroxime as First-Line Eradication Regimens for Helicobacter pylori Infection

Abstract: Esomeprazole, bismuth, levofloxacin, and amoxicillin or cefuroxime achieved similar and relatively satisfactory cure rates, safety, and compliance in first-line H. pylori eradication. Cefuroxime may be a good alternative medicine for eradication instead of amoxicillin for the patients unsuitable to take penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
1
30
2
Order By: Relevance
“…Both arms achieved similar eradication rates (84% vs 81%, p=0.513). 43 Together, these data suggest that substitution of amoxicillin with a cephalosporin may be an option for patients with a penicillin allergy. 2,9 However, eradications rates appear less than optimal for first-line therapy.…”
Section: Penicillin Allergymentioning
confidence: 90%
See 3 more Smart Citations
“…Both arms achieved similar eradication rates (84% vs 81%, p=0.513). 43 Together, these data suggest that substitution of amoxicillin with a cephalosporin may be an option for patients with a penicillin allergy. 2,9 However, eradications rates appear less than optimal for first-line therapy.…”
Section: Penicillin Allergymentioning
confidence: 90%
“…To our knowledge, only three studies have evaluated the use of a nonpenicillin β‐lactam antibiotic (e.g., cephalosporin) for the treatment of H. pylori . One small study of 12 patients found cefprozil monotherapy to be ineffective at eradicating H. pylori .…”
Section: Penicillin Allergymentioning
confidence: 99%
See 2 more Smart Citations
“…One such study reported eradication rates of 86.7% for one week of quadruple therapy including bismuth and levofloxacin compared to 72.2% for clarithromycin and bismuth and 75.56% for levofloxacin‐based triple therapy in first‐line patients . A different Chinese group observed similar eradication rates for a bismuth‐based quadruple therapy whether amoxicillin or cefuroxime was used (83.5% vs 81.0%) …”
Section: Bismuth‐based Therapymentioning
confidence: 99%